2006
DOI: 10.1002/jsfa.2721
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of African yambean (Sphenostylis stenocarpa, L): improvement by solid substrate fermentation using the tempeh fungus Rhizopus oligosporus

Abstract: The tropical African yambean (AYB, Sphenostylis stenocarpa L.) is a hardy, protein-rich under-utilised African legume. Anti-nutrients, and the excessively long cooking time (4-6 h), among other factors, limit the food use of African yambean seeds. To reduce these limitations, non-traditional, less energy consuming processing methods are required. Seeds of different varieties were (1) examined for proximate composition and (2) fermented with Rhizopus oligosporus for the production of tempeh. The traditional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
3
0
1
Order By: Relevance
“…Lima bean seeds recorded the highest phytate content (8.95 g kg −1 ) while groundnut had the lowest (3.01 g kg −1 ). Azeke et al 17 reported phytate contents of between 3 g kg −1 and 7 g kg −1 for seeds of three varieties of AYB, which is similar to the values presented in this study. The phytate content of pigeon pea seeds reported here (5.89 g kg −1 ) is lower than that reported by Oloyo18 (8.11 g kg −1 ) but higher than that reported by Sangronis and Machado19 (0.73 g kg −1 ) probably due to differences in cultivars and assay methods.…”
Section: Resultssupporting
confidence: 91%
“…Lima bean seeds recorded the highest phytate content (8.95 g kg −1 ) while groundnut had the lowest (3.01 g kg −1 ). Azeke et al 17 reported phytate contents of between 3 g kg −1 and 7 g kg −1 for seeds of three varieties of AYB, which is similar to the values presented in this study. The phytate content of pigeon pea seeds reported here (5.89 g kg −1 ) is lower than that reported by Oloyo18 (8.11 g kg −1 ) but higher than that reported by Sangronis and Machado19 (0.73 g kg −1 ) probably due to differences in cultivars and assay methods.…”
Section: Resultssupporting
confidence: 91%
“…Caramelization of the sugars may have occurred during the roasting. The preference of flavor of the treated samples to the control was in agreement with previous studies [16], [29], [30] on the importance of processing to improve traditional foods. Mailard reaction products contribute to flavor of foods [16].…”
Section: Sensory Characteristics Of the Gruelssupporting
confidence: 92%
“…In African yam bean ( Sphenostylis stenocarpa ), tempeh fermentation with 1% (v/v) citric acid added during soaking diminished cyanogenic glycoside content, which can be enzymically hydrolyzed to release cyanohydric acid that is toxic due to its ability to bind with metals, for example, Fe, Mn, and Cu (Azeke et al., 2007; Francisco & Pinotti, 2000). Tempeh fermentation is a more effective and less energy‐intensive method to prepare the African yam bean for consumption compared to the traditional preparation, which involves boiling the yam for 4 hr (Azeke et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These nonsoy tempehs are referred by mentioning the substrate before the word “tempeh,” for example, pigeon pea tempeh. Some of these other types of tempeh that have been studied are chickpeas, lentils, white beans, black beans broad beans (Erkan et al., 2020), black gram (Yadav & Khetarpaul, 1994), green grams (Lakshmy & Usha, 2010), yam‐beans (Azeke et al., 2007), velvet beans (Pugalenthi et al., 2005), rice bran (Nurrahma et al., 2018), barley (Feng et al., 2005), peanuts (Matsuo, 2006b), sunflower seeds (Vaidehi et al., 1985), lupin beans (Jiménez‐Martínez, Hernández‐Sánchez, & Dávila‐Ortiz, 2007), pigeon peas (Ali, 2008), quinoa (Matsuo, 2006a), oats (Cai et al., 2014), millet (Anandito et al., 2018), cowpeas (Lakshmy & Usha, 2010), koro benguk ( Mucuna pruriens ) (Winarni & Dharmawan, 2017), buckwheat kernels (Wronkowska et al., 2015), red sorghum (Hachmeister & Fung, 1993), wheat (Hachmeister & Fung, 1993), fava beans (Berghofer et al., 1998), peas (Ashenafi & Busse, 1991d), koro kratok bean ( Phaseolus lunatus ) (Pertiwi et al., 2020), jack bean ( Canavalia ensiformis ) (Puspitojati et al., 2019), okara (filtration residue of soymilk production) (Matsuo, 1996), finger millet ( Eleusine coracana ) (Mugula & Lyimo, 1999), cottonseed kernels, and corn grits (Matsuo, 2000).…”
Section: Resultsmentioning
confidence: 99%